2008
DOI: 10.3354/meps07648
|View full text |Cite
|
Sign up to set email alerts
|

Multi-species larval fish growth model based on temperature and fluorometrically derived RNA/DNA ratios: results from a meta-analysis

Abstract: Weight-specific growth rate (G) and growth performance (the fraction of maximum growth realized, G pf ) are key demographic characteristics. The ratio of RNA/DNA (RD) can provide information on both G and G pf . Estimating G from RD in larval fish requires an adjustment for the activity of RNA at different temperatures. Based on a meta-analysis of published data, we present a general model for the relationship between G in marine fish larvae and fluorometrically derived RD and temperature (T), and suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 47 publications
3
95
1
1
Order By: Relevance
“…Biochemical condition (RD) is one of the most widely used growth indicators for marine fish early life stages (e.g., Buckley, 1984;Buckley et al, 2008;Chícharo and Chícharo, 2008;Clemmesen et al, 2003). Recent research has standardized this ratio (sRD) allowing comparison of measurements made in different laboratories .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical condition (RD) is one of the most widely used growth indicators for marine fish early life stages (e.g., Buckley, 1984;Buckley et al, 2008;Chícharo and Chícharo, 2008;Clemmesen et al, 2003). Recent research has standardized this ratio (sRD) allowing comparison of measurements made in different laboratories .…”
Section: Discussionmentioning
confidence: 99%
“…Protein synthesis and somatic growth rates are no exception to this rule and various methods for generalization and comparison have been proposed. For example, Buckley et al (2008) reported that the best model describing instantaneous growth rates as a function of RD included a temperature interaction term (T × RD). Folkvord (2005) assessed intra-specific differences of larval cod from two distinct populations with the aid of a coupled size-temperature-growth model while Malzahn et al (2003) used degree-days to normalize the temperature dependence of somatic growth rates in North Sea houting larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative values of the Preference Index indicate a preference for coastal water, while positive values indicate a preference for lagoon water. The vertical dashed line represents the 0.8 sRD critical level determined for gilthead seabream larvae using the equations of Buckley (1984) and Buckley et al (2008).…”
Section: Ethics Statementmentioning
confidence: 99%
“…sRD ratios were converted to temperature-adjusted protein growth rates by applying the equation from Buckley (1984) and Buckley et al (2008), considering the average water temperature during the experiment (19.1 ± 1.1 • C). Thus, when larvae's protein growth rates are ≤ 0 or > 0, larvae are in poor and good nutritional condition, respectively (Robinson and Ware, 1988).…”
Section: Post-flexion Larvaementioning
confidence: 99%